RESPON PERTUMBUHAN TANAMAN KELAPA SAWIT TERHADAP PEMBERIAN TAKARAN INOKULAN FUNGI Mikoriza arbuskula (Elaeis quineensis Jacq.) VARIETAS DP SJ-1 DI PEMBIBITAN - Nafery, Rostian (Jurnal Agroekoteknologi, 2009)
ABSTRACTThis study aims tomeasure inoculation dose fungi Micoriza arbuskula on the growth of oil palm (Elais quineensis Jacq.) Varieties Dura Pesifera Sriwijaya 1 (DPSJ-1) in nurseries. Method used in research is method of experiments by using Randomized Block Design (RBD), consisting of six repeated treatment in four replication, from which 24 units of the experiment. Each treatment consisted of five plants with one plant samples victims, so the total 120 oil palm seeds. The treatment is TO = 0 g propagal per polibag, T1 = 8 g propagal per polibag, T2 = 16 g propagal per polibag, T3 = 24 g propagal per polibag, T4 = 32 g propagal per polibag, T5 = 40 g propagal per polibag. Observed variables were plant height, stem circumference, number of stem leaves, wet weight of root, and root dry weight. The results showed that, Micoriza arbuscula fungus dose of 40 g propagal per polibag able to produce growth of oil palm seed that is good height plant of 117,18 cm, plant the amount of leaf midrib strands 16.50, root dry weight of 115,57 g.Key words: Micoriza arbuscula, growth, palm oil, Elaeis quineensis Jacq.